Elevated myc expression and c-myc amplification in spontaneously occurring B lymphoid cell lines (The Rockefeller University Press, 1987)
Recently, a minor subpopulation of murine B lymphocytes, Ly-1+ B cells, has been distinguished by its unique ontogeny, tissue distribution, and prominence in certain autoimmune and neoplastic B cell diseases. We have previously described a simple murine spleen culture system that results in the spontaneous and exclusive outgrowth of long-term Ly-1+ B cell lines (B Ly-1 cells). Here, we report that the immortal growth property of B Ly-1 cells correlates with a 10-45-fold elevation of steady-state myc RNA and 2-10-fold amplification of the c-myc locus. While c-myc amplification has been observed in malignant cell lines derived from several tissues of origin, its occurrence in lymphoid cells has not been previously reported. The consistent c-myc amplification in B Ly-1 cells may reflect a unique state of this locus in the Ly-1+ B lymphocyte lineage, and contribute to the spontaneous immortalization of this B cell population in vitro, and its apparent predilection for malignant transformation in vivo.